SUSTAINABLE INTENSIFICATION IN AGRICULTURE AS A FACTOR OF ACHIEVING FOOD SECURITY - Đurić, Katarina; Njegovan, Zoran (Economics of Agriculture, 2016)
Ending hunger, achieving food security and promoting sustainable development are at the top of the list of United Nations sustainable global development priorities after 2015. In addition to many positive effects, efforts of mankind regarding the reduction of rural poverty realized through the Green Revolution have had many negative effects, primarily related to natural resources. Irreversible devastation of land, air and water quality deterioration and jeopardizing biodiversity have been recognized as key elements of unsustainability of existing agricultural development concept. Consequently, there is a need for the adoption of a new concept of agricultural development, which will lie between intensive conventional and organic farming. The concept which has already been applied in some regions of the world and whose basic goal is to fnd a way to increase production with a negligible negative impact on the environment is sustainable agricultural intensifcation. The aim of this paper is to look at both positive and negative aspects of biotechnology development so far and point out the place and role the sustainable intensifcation concept should have in relation to conservation of natural resources and achievement of food security.